2019
DOI: 10.1017/jpa.2019.12
|View full text |Cite
|
Sign up to set email alerts
|

Early Jurassic protobranch bivalves from Chubut, Argentina

Abstract: Knowledge on Early Jurassic marine fossil invertebrates from Argentina is very uneven. Particularly, faunas from Chubut Province received less attention and were thought to be poorer than those from the Neuquén Basin. Nevertheless, an updated revision of bivalves shows that some groups, such as the Protobranchia, were relatively more diverse in Chubut than in Neuquén during late Pliensbachian–early Toarcian times. Only four species are known from the southern areas of the Neuquén Basin, while seven species (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Therefore, he placed Palaeonucula as a subgenus in Nucula , and accepted Nuculoma as a genus. The general shell morphology of Palaeonucula is similar to Nucula Lamarck, but the shell is non-nacreous and has smooth shell margins (Damborenea and Pagani, 2019, p. 929). In addition, species of Nucula should be restricted to forms with radial ribbing on the shell surface, which clearly distinguishes them from both Palaeonucula and Nuculoma (Duff, 1978, p. 23).…”
Section: Systematic Paleontologymentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, he placed Palaeonucula as a subgenus in Nucula , and accepted Nuculoma as a genus. The general shell morphology of Palaeonucula is similar to Nucula Lamarck, but the shell is non-nacreous and has smooth shell margins (Damborenea and Pagani, 2019, p. 929). In addition, species of Nucula should be restricted to forms with radial ribbing on the shell surface, which clearly distinguishes them from both Palaeonucula and Nuculoma (Duff, 1978, p. 23).…”
Section: Systematic Paleontologymentioning
confidence: 99%
“…6E, F) assigned Leda decorata to Ryderia . According to Damborenea and Pagani (2019), the records of Ryderia from the Middle Jurassic of Egypt are doubtful and, therefore, they suggested that Douvillé's species probably belongs to the genus Nuculana . Based on the diagnostic features of Ryderia (a very long, narrow rostrum, a well-developed umbonal ridge, a well-developed corselet, an entire pallial line, and fine commarginal striae; Hodges, 2000, p. 40, 45), the present material (138 well-preserved specimens) can be placed in Ryderia without any doubt (Fig.…”
Section: Systematic Paleontologymentioning
confidence: 99%
See 3 more Smart Citations